THE JAVANESE TRANSLATION OF SYAIKH ʻABD AL-QĀDIR AL-JAILĀNĪ’S HAGIOGRAPHY: AN INTERTEXTUALITY ANALYSIS OF AN-NŪR AL-BURHĀNI - Abdul Munip (Analisa: Journal of Social Science and Religion, 2019)
The most famous manāqib (hagiography) of Syaikh Abd al-Qadir al-Jailānī in Java, is an-Nūr al-Burhānī, written by Kyai Muslih al-Marāqī, a Javanese translation of al-Barzanji’s al-Lujain ad-Dānī. However, this book has its uniqueness and can be regarded as a new book because Kyai Muslih is not only a translator but also a commentator of the book. This article aims to describe the relationship between the book and other text. By intertextuality analysis, this paper finds that an-Nūr al-Burhānī is a revision of some translation books of al-Lujain ad-Dāni that have existed before, as well as constructed by quotations from 30 books, 24 verses of al-Qur'an, 50 ḥadiṣ and some poems. The relationship of intertextuality is indicated by excerpt, expansion, modification, and conversion. The excerpt is seen in Kyai Muslih’s sounding about controversial issues related to Sufism. The expansion is found when he speaks more extensively about the issues he discusses. The modification is shown by shortening a lengthy ḥadiṣ, a citation, and a title of a book. The conversion is seen when he criticizes another opinion he regards as not valid. Finally, an-Nūr al-Burhānī serves as hypotext for the subsequent works. At least, two books in the Indonesian language, namely Terjemah Manaqib Syaikh Abdul Qadir Jailani by Moh Saifulloh al-Aziz and Penuntun Manaqib Syeikh Abdul Qadir al-Jailani by Baidlowi Syamsuri are the translations of Javanese an-Nūr al-Burhānī and not a direct translation of Arabic al-Lujain ad-Dāni. These findings underline the importance of the translator's competence in order to produce good translation works, as is modeled by Kyai Muslih.